Determinants Factors Associated with Working Performance among Employment at Tamansari Public Hospital - Wekadigunawan; Titta Gusni Salim; Rokiah Kusumapradja (Alta Dharma Publisher, 2021)
Introduction: Employee performance is one factor that plays an essential role in achieving company and individual goals. Objective: The study aimed to determine the determinant factors associated with employees’ performance in the Tamansari Public Hospital. Method: A cross-sectional study was applied in this study. We involved the 153 people who were randomly selected using systematic random sampling. Results: The results of this study indicated that workability and work environment was a positive association with the performance among employment in Tamansari Hospital. However, work motivation was not associated with employees’ performance. The training programs needed to improve the motivation and ability through ESQ or mental-spiritual training. The routine performance evaluations need to conduct regularly for all employees by involving Kasatpel and coordinators. Recommendation: Further study needs to conduct the study with a higher total sample using the structural equation model to confirm the factors associated with working performance